Pengaruh Model Pembelajaran Tuntas Terhadap Hasil Belajar Akidah Akhlak Materi Hidup Mulia Dengan Menghormati Orang Tua dan Guru (Studi di Kelas X MA An-Nidomiyah Cilegon) - Afiyah, Nur; Sofa, Mutiara (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Complete learning assumes that under the right conditions all students will be able to learn well and obtain maximum learning results on all the material studied. This research aims to determine the effect of the Thorough learning model on the learning outcomes of Aqidah Morals material on Living a Noble Life by Respecting Parents and Teachers. The method used in this research is a quantitative research method. The results of the calculation of the average pre-test and post-test scores can be stated that the results of learning Aqidah Akhlak in the Noble Living material by Respecting Parents and Teachers in the experimental class after the treatment was applied were from 57.00 to 82.50. Based on the research results, it can be concluded that there is a significant influence on the use of the Complete Learning model on the learning outcomes of Aqidah Morals material on Living a Noble Life by Respecting Parents and Teachers at MA An-Nidomiyah Cilegon.